2003
DOI: 10.1086/379307
|View full text |Cite
|
Sign up to set email alerts
|

Erupting Dwarf Novae in the Large Magellanic Cloud

Abstract: We report the first likely detections of erupting dwarf novae (DNe) in an external galaxy: the Large Magellanic Cloud. Six candidates were isolated from approximately a million stars observed every second night over 11 nights with the Cerro Tololo Inter-American Observatory 8K Â 8K Mosaic2 CCD imager. Artificial dwarf nova and completeness tests suggest that we are seeing only the brightest of the LMC DNe, probably SS Cygni-like cataclysmic variables (CVs), but possibly SU UMa type cataclysmics undergoing supe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Since PopI dwarf novae are located nearby the Sun, they have been found and well studied (Coppejans et al 2016;Otulakowska-Hypka et al 2016). In the case of PopII, although there have been attempts to find distant dwarf novae (possible PopII) in halo or thick disk (Hawkins & Veron 1987;Howell & Szkody 1990;Shara et al 2003), few candidates have been found because they reside at large distance from the Sun. Notably, no distance (>5 kpc from the Sun) PopII dwarf nova has been observed with light curves other than the nearby (250 pc) source SDSSJ1507+52 (Uthas et al 2011).…”
Section: Halo or Thick Disk Dwarf Novaementioning
confidence: 99%
“…Since PopI dwarf novae are located nearby the Sun, they have been found and well studied (Coppejans et al 2016;Otulakowska-Hypka et al 2016). In the case of PopII, although there have been attempts to find distant dwarf novae (possible PopII) in halo or thick disk (Hawkins & Veron 1987;Howell & Szkody 1990;Shara et al 2003), few candidates have been found because they reside at large distance from the Sun. Notably, no distance (>5 kpc from the Sun) PopII dwarf nova has been observed with light curves other than the nearby (250 pc) source SDSSJ1507+52 (Uthas et al 2011).…”
Section: Halo or Thick Disk Dwarf Novaementioning
confidence: 99%
“…All images were de-biased and flat-fielded using SOI Reduction Scripts * . With the help of the Difference Image Analysis Package (DIAPL) † , which is a modified version of DIA written by Woźniak (2000), we subtracted R-band images from images taken in the Hα filter (or vice versa if an Hα image had a lower seeing). We used the ESO Online Digital Sky Survey (DSS) to set equatorial coordinates in each image.…”
Section: Observations and Data Reductionsmentioning
confidence: 99%
“…It has one of the largest and most concentrated population of blue stragglers (over 300) ever observed in a globular cluster (Ferraro et al 1999). NGC 6093 is known to harbor two dwarf novae (DN1 and DN2, Shara et al 2005) and a classical nova (nova 1860 T Sco, Shara and Drissen 1995). The cluster's X-ray population is rich.…”
Section: Ngc 6093 (M80)mentioning
confidence: 99%
“…The second nova ever in a globular cluster; and Shara et al (2004) had to go all the way to M31 to see it (well, not literally). The first was T Sco in 1860, reported by N. R. Pogson of the magnitude system and G. F. Auwers, who owned the best-available angular diameter for the Sun at about the same time (he must have worked very long days).…”
Section: Globular Clusters (Of Stars)mentioning
confidence: 99%
“…QSO sight line with four damped Lya absorption systems (Prochaska et al 2003). dwarf nova outside the Milky Way, in the Large Magellanic Cloud (Shara et al 2003). mass-accreting T Tauri star outside the Milky Way.…”
Section: Firstsmentioning
confidence: 99%